2016
DOI: 10.1007/s00792-016-0826-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the complete genome sequence of the archaeon Pyrococcus chitonophagus DSM 10152 (formerly Thermococcus chitonophagus)

Abstract: Here we analyze the first complete genome sequence of Pyrococcus chitonophagus. The archaeon was previously suggested to belong to the Thermococcus rather than the Pyrococcus genus. Whole genome phylogeny as well as whole proteome comparisons using all available complete genomes in Thermococcales clearly showed that the species belongs to the Pyrococcus genus. P. chitonophagus was originally isolated from a hydrothermal vent site and it has been described to effectively degrade chitin debris, and therefore is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Multiple samples of spider exoskeleton, including fragments of cuticle and setae, were incubated with four chitinases: Chi60 from M. marina and its deletion mutant, missing two Ig-like domains [101] and two chitinases, Chiton_1119 and Chiton_1716, from P. chitonophagus [102]. The samples were incubated with the enzymes at 18, 28, and subsequently 35 °C, for at least 48 h at each temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple samples of spider exoskeleton, including fragments of cuticle and setae, were incubated with four chitinases: Chi60 from M. marina and its deletion mutant, missing two Ig-like domains [101] and two chitinases, Chiton_1119 and Chiton_1716, from P. chitonophagus [102]. The samples were incubated with the enzymes at 18, 28, and subsequently 35 °C, for at least 48 h at each temperature.…”
Section: Methodsmentioning
confidence: 99%
“…chitonophagus is known to possess multiple chitinases (40)(41)(42). Recently, two groups of investigators have conducted genome analyses of this archaeon, and both predicted the presence of three chitinase genes (43,44). Reclassification of the organism to the genus Pyrococcus has also been proposed (species name Pyrococcus chitonophagus) (43).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two groups of investigators have conducted genome analyses of this archaeon, and both predicted the presence of three chitinase genes (43,44). Reclassification of the organism to the genus Pyrococcus has also been proposed (species name Pyrococcus chitonophagus) (43). Biochemical characterization of one of the T. chitonophagus chitinases, ChiD, has revealed that the enzyme is a structurally novel chitinase exhibiting exo-type activities and mainly releases (GlcNAc) 2 units from the reducing ends of chitin chains (44).…”
Section: Discussionmentioning
confidence: 99%
“…All gene clusters related to chitin utilization are absent in Pa. pacificus, different to Pyrococcus and Thermococcus, such as P. furious [22], P. chitonophagus [23] and T. kodakaraensis KOD [24]. The lipolytic growth of T. sibiricus appears to be unique in the order Thermococcales [20].…”
Section: Utilization Of Carbohydratesmentioning
confidence: 99%